Evaluating refrigeration and antibiotic treatment for maintaining urine electrophysiology. - Rashedul Hoque; Fatima H Labeed; Srdjan Cirovic; Michael Pycraft Hughes (PLoS ONE)
Background Electrophysiological analysis of urine has shown utility in differentiating between healthy and bladder cancer specimens, offering a rapid, label-free alternative to molecular methods. However, transporting and preserving urine samples from collection to the laboratory poses logistical challenges that could impact the reliability of electrophysiological measurements. Objective This study investigates the effects of prolonged refrigeration on the dielectric properties and ζ-potential of urine specimens and evaluate whether antibiotic treatment can enhance sample preservation without altering electrophysiological properties. A new methodology to evaluate urine specimen quality and determine bacterial contamination, using electrophysiological modalities, is presented. Methods Mid-stream urine samples from healthy participants (n =  4) were collected and divided into untreated and 1% penicillin/streptomycin-treated groups. Samples were analysed at baseline prior to storage at 4°C, with further analysis every 24 hours for 96 hours. Changes in dielectrophoresis (DEP) response and ζ-potential were measured using a 3DEP cytometer (Deparator, UK) and Malvern Panalytical Zetasizer Nano ZS90 (Malvern, UK), respectively. Chemical analyses, including pH and nitrite levels, and microscopic examinations were also conducted. Results & limitations Significant electrophysiological changes were observed in both untreated and antibiotic-treated urine samples over time. Both groups showed a linear increase of change in DEP response and ζ-potential values, from baseline over time. Untreated samples exhibited significant deviations in DEP and ζ-potential from baseline after 48 hours, with significance at 72 hours (P < 0.05). Treated samples only showed significant changes in ζ-potential at 96 hours (P < 0.05). Chemical analysis indicated increased pH and nitrite presence in untreated samples at 48 hours, indicating bacterial growth. Treated samples took more than 48 hours to show changes in both chemical parameters. Limitations include the relatively small study sample size, not evaluating the preservatory effects of UTI-specific antibiotics, such as nitrofurantoin and trimethoprim, and exploring different drug concentrations. Conclusion Prolonged refrigeration can maintain the quality of urine samples for up to 48 hours with antibiotic treatment. Current UK and European guidelines recommend urinalysis within 24 hours of specimen collection; the findings of this study support the use of DEP and ζ-potential analysis as practical clinical tests in a mail-in screening setting, provided appropriate sample preservation measures are taken.